Composite material, preparation method thereof and implant
By combining piezoelectric materials with metal ion-releasing materials, piezoelectric response is used to achieve intelligent degradation, which solves the problem that existing bone implants cannot adaptively degrade and provides personalized fracture healing solutions.
Patent Information
- Application Number
- CN202411763473.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-30
- Filing Date
- 2024-12-03
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The existing degradable bone implants cannot adaptively intelligently degrade according to the recovery conditions of different patients, and cannot meet the special needs of patients in different conditions and age groups.
The composite material prepared by the composite of the composite of the piezoelectric material and the metal ion release material is used to intelligently degrade the metal ion to release the material through the voltage response, and adjust the degradation rate according to the patient's recovery.
The adaptive degradation of implants at different restoration stages provided the initial stable and fixed effect, and gradually degraded with the healing of the bone tissue, met the patient's personalized needs, and improved the healing efficiency of the fracture site.
Smart Images

Figure HDA0005168268330000011 
Figure HDA0005168268330000012 
Figure HDA0005168268330000021
Abstract
Description
[0001] This application claims priority to the Chinese patent application filed with the China Patent Office on May 30, 2024, with application number: 202410689865.7, and invention name: "A composite material, its preparation method and implant", the entire content of which is incorporated by reference into this application. Technical Field
[0002] The present invention relates to the technical field of medical materials, and in particular to a composite material, a preparation method thereof, and an implant. Background Art
[0003] Fractures are the most common accidental injuries in human daily life. If the patient's injury is more serious, resulting in a complete fracture of the damaged part, internal fixation of the fracture is required, and the fracture site is fixed and protected by bone screws and bone plates. At present, such bone implants used in orthopedic clinics are still mainly made of titanium alloy. Although titanium alloy has good biocompatibility and corrosion resistance, its rigidity is too high, which can easily induce stress shielding effect, leading to secondary fractures in patients after surgery. In addition, titanium alloy is a non-degradable material, and most patients need a second operation to remove it after recovery, which increases the pain of the operation and the risk of postoperative infection. If the implant is not removed, it will exist in the body for a long time, and may release harmful ions or metal particles due to wear or corrosion, causing inflammation, allergies and other reactions in the human body.
[0004] Based on the above problems, researchers are committed to developing more suitable bone implant materials, and then started research on magnesium alloys. First, the elastic modulus and density of magnesium alloys are closer to human bones, which can effectively avoid the stress shielding effect. Secondly, magnesium alloys are degradable and bioactive, and their degradation products can promote osteogenesis and antibacterial. Although these inherent properties of magnesium alloys effectively avoid the defects of titanium alloys in clinical applications, it also has the biggest problem. Its degradation rate is too fast and uncontrollable, which will cause its mechanical properties to drop suddenly and hydrogen will be released during the degradation process, which is not conducive to bone tissue repair at the fracture site. It is this problem that limits its application in bone implants. Therefore, it is particularly important to develop absorbable bone implants with a suitable degradation rate.
[0005] Patent CN110449579A discloses a controllable degradation zinc-magnesium gradient material, which uses magnesium powder and zinc powder as raw materials and is prepared by spark plasma sintering. In vitro immersion degradation experiments show that the average degradation rate of the gradient material in the early stage (3 months) is only 1.188mm / a, while the degradation rate in the later stage (6 months) increases significantly, reaching 62.101mm / a. Although the invention achieves the change of degradation rate through the gradient strategy, it can achieve the unique functional requirements of corrosion resistance of the outer layer material in the early stage of implantation, ensure the overall mechanical properties, and rapid degradation in the later stage of implantation, but it cannot match the particularity of patients with different conditions and different age groups, and cannot make adaptive intelligent degradation according to the recovery conditions of different patients.
[0006] Patent CN111334688A discloses a biodegradable Zn-RE zinc alloy material. The material's primary element is Zn, and the alloying element is one of the non-radioactive rare earth elements (RE). The RE content, measured by mass, is 0-3%, excluding zero. The balance is zinc. The non-radioactive RE elements include scandium (Sc), yttrium (Y), lanthanum (139La), cerium (Ce), praseodymium (Pr), neodymium (Nd), samarium (150Sm), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (175Lu). The material is produced by hot extrusion. Electrochemical experimental data show that the degradation rate of these alloys is in the range of 0.02-2.85mm / a. Although the degradation performance can be adjusted by changing the type of rare earth elements added, the ideal implant should have a corresponding degradation rate during different recovery periods of the human body. The Zn-RE zinc alloy material in this invention cannot meet this unique functional requirement.
[0007] Amorphous alloys generally have excellent corrosion resistance due to their structural uniformity (no grain boundaries, dislocations, or precipitates). The elastic modulus of MgZnCa in Mg-based amorphous alloys is closely matched to that of human bones, making them biodegradable and having better corrosion resistance than traditional magnesium alloys. F. et al. studied the hydrogen evolution of MgZnCa amorphous strips with different zinc contents. The results showed that Mg 60 Zn 35 Ca5 has the best corrosion resistance. After being immersed in SBF solution for 70 hours, no hydrogen is released. In contrast, the hydrogen release rate of pure magnesium is as high as 18 mL / cm 2 Similarly, in the in vivo hydrogen evolution experiment, Mg 60 Zn 35 No hydrogen is generated around the Ca5 band, but a large amount of hydrogen is generated around WZ21. F. The research team also prepared Mg60 Zn 35 Ca5 amorphous rods (1.6*3mm) were used to study their degradation in vivo. 60 Zn 35 After 90 days of implantation into the mouse tibia, Ca5 showed no hydrogen evolution or degradation, and the surrounding new bone tissue was continuous and intact.
[0008] Piezoelectric crystals are materials with asymmetric crystal structures, such as barium titanate (BTO), zinc oxide (ZnO), and aluminum nitride (AlN). When deformed by an external force, they experience internal polarization, with opposite charges appearing on their two opposing surfaces. When the external force is removed, they return to a neutral state. This conversion of mechanical energy into electrical energy is known as the positive piezoelectric effect.
[0009] The biodegradable bone implants of the existing technology are non-ideal and non-intelligent. They are unable to adapt to the specific needs of patients with different conditions and age groups and are unable to make adaptive intelligent degradation. The ideal biodegradable bone implant needs to provide a relatively solid fixation in the initial stage of postoperative fixation to provide a stable mechanical environment for the fracture site. Then, as the implant continues to degrade, its stiffness continues to decrease. At the same time, the bone tissue continues to heal, gradually taking on more load, thereby promoting the effect of bone growth. Ultimately, the implant is completely degraded and replaced by new bone, and no further removal is required. Therefore, the development of an intelligent biodegradable implant that can degrade according to the patient's own recovery level will be more clinically valuable. Summary of the Invention
[0010] In view of this, the technical problem to be solved by the present invention is to provide a composite material, a preparation method thereof, and an implant. The composite material can intelligently degrade a metal ion-releasing material through the piezoelectric response of the piezoelectric material.
[0011] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0012] The invention provides a composite material obtained by compounding a piezoelectric material and a metal ion releasing material.
[0013] The metal ion releasing material is selected from one or more of magnesium-based degradable alloys, iron and iron-based degradable alloys, zinc and zinc-based degradable alloys.
[0014] The present invention has no particular limitation on the above-mentioned compounding, and common compounding methods such as doping or deposition may be used.
[0015] In some specific embodiments of the present invention, preferably, the composite is performed by doping or deposition.
[0016] The piezoelectric material in the composite material generates electric charges in response to pressure, which promote the degradation of the metal ion-releasing material to release metal ions. The generation of electric charges and the release of metal ions together promote the healing of the implant site.
[0017] In the present invention, the piezoelectric material in the composite material preferably accounts for 1% to 15% by mass, more preferably 5% to 10% by mass, and in some specific embodiments of the present invention, preferably 8% by mass.
[0018] In the present invention, preferably, the piezoelectric material is selected from tetragonal barium titanate (T-BTO), zinc oxide, and molybdenum sulfide; more preferably, it is tetragonal barium titanate.
[0019] Preferably, the magnesium-based degradable alloy is selected from Mg 60 Zn 35 One or more of Ca5 amorphous alloy, MgZnCaSr amorphous alloy, MgZnYNd alloy, MgYReZr alloy, MgZnCa alloy, MgZnSr alloy, MgZnCaSr alloy, and MgZnCu alloy; more preferably Mg 60 Zn 35 Ca5 amorphous alloy.
[0020] Preferably, the iron-based degradable alloy is selected from FeZn series alloys and / or FeMn series alloys.
[0021] The FeZn series alloys include but are not limited to Fe-15Zn.
[0022] The FeMn series alloys include but are not limited to FeMnAg alloys, FeMnCu alloys, FeMnSi alloys, FeMnSiCa alloys, and the like.
[0023] Preferably, the zinc-based degradable alloy is selected from one or more of ZnMg series alloys, ZnCa series alloys, ZnCu series alloys, ZnMn series alloys, ZnLi series alloys, and ZnRe series alloys; more preferably, it is a ZnMg alloy.
[0024] The ZnCu series alloys include but are not limited to Zn-3Cu, Zn-3Cu-0.5Fe, Zn-3Cu-0.5Mg, etc.
[0025] The ZnMg series alloys include but are not limited to Zn-0.8Mg, Zn–3Mg, Zn-1Mg-1Sr, Zn-1Mg-0.1Mn, Zn–1Mg–1Ca, etc.
[0026] The ZnCa series alloys include but are not limited to Zn–1Ca–1Sr.
[0027] The ZnMn series alloys include but are not limited to Zn-0.1Mn.
[0028] The ZnLi series alloys include but are not limited to Zn-0.4Li, Zn-0.5Li, Zn-0.8Li, Zn-0.8Li-0.2Ag, etc.
[0029] The ZnRe series alloys include but are not limited to Zn-0.2La, Zn-0.2Y, Zn-0.2Ce, Zn-0.2Nd, Zn-0.2Ho, Zn-0.2Lu, etc.
[0030] The numerical values before the metal elements in the above series of alloys represent the mass percentage of the element in the alloy.
[0031] Preferably, the piezoelectric material is selected from tetragonal barium titanate, and the metal ion releasing material is selected from Mg 60 Zn 35 One or more of Ca5 amorphous alloy, iron, zinc, and zinc-based degradable alloy.
[0032] Preferably, the zinc-based degradable alloy is selected from Zn-Mg alloy, wherein the mass percentage of Mg is 0.1% to 0.8%, more preferably 0.8%.
[0033] When the metal ion releasing material is selected from Mg 60 Zn 35 When the Ca5 amorphous alloy is used, the composite material is represented by T-BTO-Mg 60 Zn 35 Ca5 composite material.
[0034] In some specific embodiments of the present invention, the T-BTO-Mg 60 Zn 35 The Ca5 composite material is prepared by compounding a metal ion releasing material on the surface of a piezoelectric material. 60 Zn 35 The thickness of the piezoelectric material T-BTO layer in the Ca5 composite material is 370nm, and the metal ion release material Mg 60 Zn 35 The thickness of the Ca5 layer is 4.03 μm.
[0035] When the metal ion releasing material is selected from iron, the composite material is expressed as a T-BTO-Fe composite material.
[0036] When the metal ion releasing material is selected from a zinc-based degradable alloy, the composite material is expressed as a T-BTO-Zn-0.8Mg composite material, wherein the zinc-based degradable alloy is selected from Zn-0.8Mg, and the mass ratio of Zn to Mg is 99.2%:0.8%.
[0037] The present invention also provides a method for preparing the composite material, comprising the following steps:
[0038] The composite material is obtained by compounding the piezoelectric material and the metal ion releasing material through a magnetron sputtering method, a melting method or a 3D printing method.
[0039] The composite material obtained by the magnetron sputtering method consists of a piezoelectric material layer and a metal ion releasing material layer.
[0040] Preferably, the magnetron sputtering method of the present invention comprises uniformly sputtering the piezoelectric material onto the surface of the substrate by a first magnetron sputtering and then uniformly sputtering the metal ion releasing material onto the surface of the piezoelectric material by a second magnetron sputtering to prepare the composite material.
[0041] The first magnetron sputtering and the second magnetron sputtering are preferably performed under an inert gas atmosphere.
[0042] Preferably, the inert gas includes but is not limited to argon, helium, neon, tritium, etc.
[0043] Preferably, the inert gas is selected from argon.
[0044] Preferably, the vacuum degree of the vacuum environment is 3*10 -4 ~8*10 -3 Pa; more preferably 5*10 -4 ~9*10 - 4 Pa; more preferably 5*10 -4 Pa.
[0045] Preferably, the first magnetron sputtering and the second magnetron sputtering are performed using a DC power supply or a radio frequency power supply;
[0046] Preferably, the power of the DC power supply or radio frequency power supply is 50 to 150 W; more preferably 90 to 120 W; further preferably 100 W.
[0047] Preferably, the pressure of the first magnetron sputtering or the second magnetron sputtering is 0.5-1.8 Pa, more preferably 0.8-1.5 Pa, and even more preferably 0.8 Pa. In some specific embodiments of the present invention, the pressure of the first magnetron sputtering is preferably 1.5 Pa, and the pressure of the second magnetron sputtering is preferably 0.8 Pa.
[0048] Preferably, the duration of the first magnetron sputtering or the second magnetron sputtering is 0.3 to 3 hours. More preferably, it is 0.5 to 2 hours; and even more preferably, it is 0.5 hours. In some specific embodiments of the present invention, the duration of the first magnetron sputtering is preferably 2 hours, and the duration of the second magnetron sputtering is preferably 0.5 hours.
[0049] The magnetron sputtering includes processes such as ion bombardment and deposition.
[0050] In the present invention, the magnetron sputtering preparation method preferably comprises the following steps:
[0051] 1) Under the action of the electric field, electrons are accelerated to fly toward the substrate and collide with argon atoms, causing the argon atoms to ionize and generate a large number of argon ions and new electrons.
[0052] 2) The new electrons continue to fly toward the substrate, while the argon ions are accelerated under the action of the electric field to bombard the surface of the metal ion-releasing material, so that the neutral atoms or molecules on the surface of the metal ion-releasing material obtain sufficient kinetic energy, detach from the material surface, and deposit on the surface of the piezoelectric material to form a metal ion-releasing material layer, thereby preparing the composite material.
[0053] Preferably, in the present invention, the smelting method comprises mixing and smelting the metal ion releasing material and the piezoelectric material to obtain the composite material.
[0054] The 3D printing method includes uniformly mixing piezoelectric material powder and metal ion releasing material powder, and then performing laser melting molding through 3D printing to obtain the composite material.
[0055] The composite material obtained by the above-mentioned melting method and 3D printing is a doped composite material.
[0056] The present invention also provides an implant comprising the composite material or the composite material prepared by the above preparation method.
[0057] In the above implant, the piezoelectric material in the composite material is preferably a material with stable physicochemical properties, excellent piezoelectric performance and good biocompatibility.
[0058] In the present invention, the piezoelectric material in the composite material is preferably tetragonal barium titanate, zinc oxide, or molybdenum sulfide. While tetragonal barium titanate (T-BTO) does not degrade, once the metal ion-releasing material in the composite material degrades, the T-BTO is excreted from the body, minimizing harm to the human body. Zinc oxide or molybdenum sulfide, when used as piezoelectric materials in implants, degrades, and the metal ions produced by degradation also pose minimal harm to the body.
[0059] The present invention also provides the use of the above-mentioned implant in biomedical degradable stents, biomedical degradable suture materials, degradable orthopedic implants, degradable dental materials, degradable self-powered electronic bandages, and degradable electrodes.
[0060] The biomedical degradable stent includes but is not limited to a tracheal stent, an esophageal stent, an intestinal stent, a vascular stent, a biliary stent or a urethral stent.
[0061] The biomedical degradable suture materials include but are not limited to absorbable skin suture staples, absorbable suture threads or medical zippers.
[0062] The degradable orthopedic implants include but are not limited to bone plates, intramedullary nails, screws, bone needles, spinal fixation devices, ligature wires, patellar concentrators, bone repair materials, bone tissue repair scaffolds, etc.
[0063] The degradable dental material includes but is not limited to dental implant materials or root canal files. When the composite material is used as a degradable orthopedic implant, the metal ion-releasing material in the composite material can intelligently degrade according to the piezoelectric response to meet the needs of patients at different bone recovery stages.
[0064] In the early postoperative period, the patient's limb cannot be subjected to stress. At this time, the composite material of the present invention provides excellent fixation for the patient's fractured limb. As the patient recovers, the fractured limb begins to be subjected to stress. This stress acts on the piezoelectric material, causing it to generate microcurrents in the metal ion-releasing material. These microcurrents promote the degradation of the metal ion-releasing material, causing it to release metal ions, thereby promoting bone growth at the fracture site. Furthermore, the degradation rate of the metal ion-releasing material can be adaptively adjusted based on the amount of stress applied to the patient's fractured limb, intelligently degrading while promoting recovery at the fracture site.
[0065] In the present invention, when the composite material is selected from the T-BTO-Zn-0.8Mg composite material, when the patient's limb cannot bear the force, the T-BTO-Zn-0.8Mg provides a good fixation effect for the patient's fracture site. As the fractured limb begins to bear the force, the stress acts on the piezoelectric material T-BTO, causing the T-BTO to generate a microcurrent in the Zn-0.8Mg alloy. The microcurrent can promote the degradation of the Zn-0.8Mg alloy, causing it to release Mg 2+ and Zn 2+ , thereby promoting bone growth at the fracture site. 2+ and Zn 2+ The amount of release is determined by the different forces applied to the patient's limbs, thus satisfying the adaptive intelligent degradation requirements for the patient.
[0066] Compared to existing technologies, the composite material provided by the present invention is formed by combining a piezoelectric material and a metal ion-releasing material; the metal ion-releasing material is selected from one or more of magnesium-based biodegradable alloys, iron and iron-based biodegradable alloys, and zinc and zinc-based biodegradable alloys. This composite material, through the piezoelectric response of the piezoelectric material, adaptively generates microcurrents of varying magnitudes at different stages of a patient's recovery. This microcurrent promotes the intelligent degradation of the metal ion-releasing material, aligning with the patient's own recovery. The resulting metal ions and the microcurrent jointly promote healing at the implant site, which has important implications for the development and application of implant materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 The T-BTO-Mg prepared in Example 1 60 Zn 35 Structural characterization diagram of Ca5 composite material, where a is XRD diagram, b is TEM diagram, and c is EDS spectrum diagram;
[0068] Figure 2 Figures 1 and 2 are piezoelectric performance test diagrams of the T-BTO coating prepared in Example 1 under different stresses, wherein Figure a is a piezoelectric response phase hysteresis loop diagram, Figure b is an amplitude butterfly loop diagram, Figures c, d, and e are piezoelectric response diagrams at stresses of 0.1N, 0.2N, and 0.3N, respectively, and Figure f is a voltage test schematic diagram;
[0069] Figure 3 The degradation performance test diagram of different composite materials under different stresses, where a is BTO-Mg 60 Zn 35 SEM images of Ca5 composite material degradation under cyclic dynamic load (0.3N, 1.25Hz) for 10 minutes, b is BTO-Mg 60 Zn 35 Schematic diagram of the laboratory where dynamic load is applied to Ca5 composite material, c is the weight loss rate diagram of the composite material under different stresses;
[0070] Figure 4 This is an SEM image of the BTO-Zn composite material prepared in Example 2 after degradation under cyclic dynamic load (0.3N, 1.25Hz) for 1 hour;
[0071] Figure 5 This is a graph showing the weight loss rate of the BTO-Zn composite material prepared in Example 2 under cyclic dynamic load (0.3N, 1.25Hz);
[0072] Figure 6 This is an SEM image of the BTO-Fe composite material prepared in Example 3 after degradation under cyclic dynamic load (0.3N, 1.25Hz) for 5 hours;
[0073] Figure 7 This is a graph showing the weight loss rate of the BTO-Fe composite material prepared in Example 3 under cyclic dynamic load (0.3N, 1.25Hz);
[0074] Figure 8 Figure 4 is a structural characterization diagram of the T-BTO-Zn-0.8Mg composite material prepared in Example 4, a is an XRD diagram, and b is a distribution diagram of T-BTO in the alloy;
[0075] Figure 9 Figure 4 is a piezoelectric characteristic diagram of the T-BTO particles in Example 4, Figure a is a piezoelectric response phase hysteresis loop diagram, and Figure b is an amplitude butterfly loop diagram;
[0076] Figure 10 These are the degradation performance characterization diagrams of the T-BTO-Zn-0.8Mg composite material prepared in Example 4, where a is the test device diagram and b is the average weight loss rate diagram. DETAILED DESCRIPTION
[0077] In order to further illustrate the present invention, the composite material, its preparation method and implant provided by the present invention are described in detail below with reference to the examples.
[0078] The following Mg 60 Zn 35 Ca5 is abbreviated as MgZnCa in the accompanying drawings.
[0079] (1) Preparation of composite materials
[0080] Example 1
[0081] (1) Preparation of amorphous BTO coating
[0082] A layer of amorphous BTO (A-BTO) was sputtered on a 301 stainless steel substrate (36*6*0.15mm (length*width*thickness)) by magnetron sputtering technology. The parameters of the magnetron sputtering technology are as follows: RF power supply with a power of 100W, vacuum degree of 5*10 -4 Pa, the sputtering atmosphere is argon atmosphere, the pressure is 1.5 Pa, and the sputtering time is 2 h.
[0083] (2) Preparation of tetragonal BTO coating
[0084] The amorphous BTO (A-BTO) was annealed at 700° C. for 15 min to obtain tetragonal BTO (T-BTO).
[0085] (3) Preparation of composite materials
[0086] The tetragonal BTO (T-BTO) prepared in (2) was used as a substrate and Mg was sputtered on its surface. 60 Zn 35 Ca5, that is, T-BTO-Mg 60 Zn 35 Ca5 composite material, in which sputtered Mg 60 Zn 35 The parameters of Ca5 are as follows: a DC power supply with a power of 100 W, a vacuum degree of 5*10-4 Pa, an argon atmosphere with a pressure of 0.8 Pa, and a sputtering time of 0.5 h.
[0087] Example 2
[0088] The preparation process of T-BTO-Zn composite material is as follows:
[0089] The prepared tetragonal BTO (T-BTO) was used as a substrate, and Zn was sputtered on its surface to obtain a T-BTO-Zn composite material. The parameters for sputtering Zn were as follows: a DC power supply with a power of 100 W, a vacuum degree of 5*10-4 Pa, an argon atmosphere with a pressure of 1.6 Pa, and a sputtering time of 1 h.
[0090] Example 3
[0091] The preparation process of T-BTO-Fe composite material is as follows:
[0092] The prepared tetragonal BTO (T-BTO) was used as a substrate, and Fe was sputtered on its surface to obtain a T-BTO-Fe composite material, wherein the parameters for sputtering Fe were as follows: a DC power supply with a power of 100 W, a vacuum degree of 5*10-4 Pa, an argon atmosphere with a pressure of 0.6 Pa, and a sputtering time of 1 h.
[0093] Example 4
[0094] Raw materials: Zinc particles and magnesium particles (purity: 99.996) were purchased from Hebei Qinbang New Materials Technology Co., Ltd., and tetragonal barium titanate powder (particle size: 0.5-1 μm) was purchased from Shanghai Buwei Applied Materials Technology Co., Ltd.
[0095] 1) Preparation of Zn-0.8Mg alloy: Zinc and magnesium particles were added in a mass percentage ratio of 99.2%:0.8%, and smelted in an induction melting furnace with a vacuum degree of 8*10 -3 Pa, the melting atmosphere is argon atmosphere, and the pressure is -0.05Mpa.
[0096] 2) Preparation of T-BTO-Zn-0.8Mg composite material: Weigh 200g of zinc and magnesium particles with a mass percentage of 99.2%:0.8%, then shake and mix 3g of tetragonal barium titanate powder with metallic zinc and magnesium particles to make the surface of metallic zinc and magnesium particles evenly adsorb the tetragonal barium titanate powder, and then melt it in an induction melting furnace with a vacuum degree of 8*10 -3 Pa, the melting atmosphere is argon atmosphere, and the pressure is -0.05Mpa.
[0097] Comparative Example 1
[0098] The amorphous BTO (A-BTO) prepared in step (1) of Example 1 was used as a substrate, and Mg was sputtered on its surface. 60 Zn 35 Ca5, that is, A-BTO-Mg 60 Zn 35 Ca5 composite material (abbreviated as A-BTO-MgZnCa), in which sputtered Mg 60 Zn 35 The parameters of Ca5 are as follows: a DC power supply with a power of 100 W, a vacuum degree of 5*10-4 Pa, an argon atmosphere with a pressure of 0.8 Pa, and a sputtering time of 0.5 h.
[0099] Comparative Example 2
[0100] The same as Example 2, except that amorphous BTO (A-BTO) is used as the substrate to obtain an A-BTO-Zn composite material.
[0101] Comparative Example 3
[0102] The same as Example 3, except that amorphous BTO (A-BTO) is used as the substrate to obtain an A-BTO-Fe composite material.
[0103] (2) Performance test results
[0104] The T-BTO-Mg prepared in Example 1 60 Zn 35 The structural characterization of Ca5 composite material (abbreviated as T-BTO-MgZnCa) was obtained Figure 1 Among them, Figure a is T-BTO-Mg 60 Zn 35 The XRD pattern of the Ca5 composite material shows that the diffraction peaks of the composite material at (100), (110), (111), (211) and (200) planes are consistent with those of tetragonal T-BTO, and the Mg deposited on the surface of tetragonal T-BTO is 60 Zn 35Ca5 is a typical amorphous structure, which has a distinct broadening peak between 30° and 45° and no obvious crystal diffraction peak. 60 Zn 35 The thickness and microstructure of each layer in the Ca5 composite material were observed by TEM after the sample was processed by FIB (Fig. 60 Zn 35 The thickness of Ca5 is about 4.03μm, and the thickness of BTO is about 370nm. Figure c is the EDS spectrum, and the results show that Mg, Zn, Ca, Ba, Ti and O elements are evenly distributed. In summary, Example 1 successfully prepared T-BTO-Mg 60 Zn 35 Ca5 composite material.
[0105] The piezoelectric performance test results of the tetragonal BTO coating prepared in Example 1 were performed using a piezoresistive force microscope (PFM). Figure 2 As shown. Figure a is the piezoelectric response phase hysteresis loop diagram, and the results show that the phase voltage signal of T-BTO has an obvious 180° phase shift; Figure b is the amplitude butterfly loop diagram, and the results show that a butterfly-shaped hysteresis loop is obtained in the voltage range of -5V to 5V, indicating that the T-BTO we prepared has a typical piezoelectric response; Subsequently, the voltage response of the T-BTO film under different stresses was tested by an oscilloscope (YOKOGAWADL850). Under stresses of 0.1N (Figure c), 0.2N (Figure d) and 0.3N (Figure e), the T-BTO coating generated output voltages of about 0.5V, 1.0V and 1.5V respectively; Figure f is a schematic diagram of the voltage test. Under stress, T-BTO-Mg 60 Zn 35 Polarization occurs inside the T-BTO in the Ca5 composite material, resulting in opposite positive and negative charges on its two opposite surfaces.
[0106] The T-BTO-Mg prepared above 60 Zn 35 Ca5 composite material (Example 1) and T-BTO-Mg 60 Zn 35 The Ca5 composite material (Comparative Example 1) was immersed in a 37°C PBS buffer solution, and a dynamic load (0.3N, 1.25Hz) was applied to it to test the degradation performance of the composite material under different stresses. Figure 3 As shown in Figure b, Figure b is BTO-Mg 60 Zn 35 Schematic diagram of the experiment of Ca5 composite material under dynamic load, in which BTO-Mg 60 Zn 35Ca5 composite material is T-BTO-Mg 60 Zn 35 Ca5 composite material or A-BTO-Mg 60 Zn 35 After 10 minutes of action, the samples were taken out and the corrosion products on their surfaces were cleaned with 5% chromic acid solution. The corrosion conditions of the samples were then observed by SEM. The two groups of samples were A-BTO-Mg without piezoelectric effect and 60 Zn 35 Ca5, and T-BTO-Mg with piezoelectric effect 60 Zn 35 Ca5, as shown in Figure a, the identification of coating elements by EDS energy spectrum shows that under the same stress, T-BTO-Mg 60 Zn 35 The BTO in the Ca5 coating is more exposed, indicating that the Mg 60 Zn 35 Ca5 degrades more, proving that the piezoelectric effect can indeed promote the growth of Mg under stress. 60 Zn 35 Degradation of Ca5. Moreover, the middle of the same sample degrades more than the two ends. This is because during the experiment, the middle of the sample is directly subjected to force, and the stress towards the two ends gradually decreases. In addition, by applying different stresses (0.1N, 0.2N or 0.3N) to the composite material, after degradation for 10 minutes, the corrosion products on its surface are washed away with 5% chromic acid solution, and the mass before and after degradation is weighed by an analytical balance. The weight loss rate of the coating under different stresses is calculated (weight loss rate = (mass of the coating before degradation - mass of the coating after degradation) / surface area of the coating). The results are shown in Figure c. Under three stresses, T-BTO-Mg 60 Zn 35 Mg in Ca5 60 Zn 35 The degradation of Ca5 was better than that of A-BTO-Mg 60 Zn 35 The content of Ca5 is higher, and the difference between the two becomes larger with the increase of stress. This is because as the stress increases, the current generated by T-BTO is larger, which can further promote degradation.
[0107] In summary Figures 1 to 3 It can be seen that the present invention successfully prepared T-BTO-Mg 60 Zn 35 Ca5 composite materials, different stresses will cause T-BTO to generate corresponding currents, thereby promoting Mg 60 Zn 35 Ca5 undergoes varying degrees of degradation, a stress-responsive intelligent degradation.
[0108] The degradation performance of BTO-Zn composite materials under cyclic dynamic load (0.3N, 1.25Hz) was tested. Figure 4 , Figure 4 The following is an SEM image of the degradation of a BTO-Zn composite material under a cyclic dynamic load (0.3N, 1.25Hz) for 1 hour. The BTO-Zn composite materials are T-BTO-Zn composite material (Example 2) and A-BTO-Zn composite material (Comparative Example 2). The results show that under the same stress, the BTO in the T-BTO-Zn coating is more exposed, indicating that the Zn degradation on its surface is greater. That is, under the same stress, the degree of Zn degradation in T-BTO-Zn is greater than that in A-BTO-Zn. This is because T-BTO has a piezoelectric effect, and the current it generates better promotes the degradation of Zn on the surface of the composite material.
[0109] Figure 5 This is a graph of the weight loss rate of BTO-Zn composite materials (T-BTO-Zn composite material and A-BTO-Zn composite material) under a stress of 0.3N and 1.25Hz. The results show that under the same stress, Zn degradation in the T-BTO-Zn coating is greater.
[0110] comprehensive Figure 4 、 5 It can be seen that under stress, the piezoelectric effect can also promote the degradation of Zn.
[0111] The degradation performance of BTO-Fe composite materials under cyclic dynamic load (0.3N, 1.25Hz) was tested. Figure 6 , Figure 6 The following are SEM images of the degradation of BTO-Fe composite materials (T-BTO-Fe composite material (Example 3) and A-BTO-Fe composite material (Comparative Example 3)) under cyclic dynamic load (0.3N, 1.25Hz) for 5 hours. The results show that under the same stress, the BTO in the T-BTO-Fe composite material is more exposed, indicating that the Fe on its surface is more degraded.
[0112] Figure 7 The weight loss rate of the BTO-Fe composite material under cyclic dynamic loading (0.3N, 1.25Hz) is shown in Figure 2. The results show that under the same stress, the Fe in the T-BTO-Fe coating degrades more.
[0113] comprehensive Figure 6 、 7 It can be seen that under stress, the piezoelectric effect can also promote the degradation of Fe.
[0114] First, XRD tests were performed on the T-BTO particles used in Example 4 and the synthesized Zn-0.8Mg and T-BTO-Zn-0.8Mg composite materials. Figure 8 As shown in a, the T-BTO particles used are tetragonal barium titanate with piezoelectric effect, and the magnesium in Zn-0.8Mg is in the form of an intermetallic compound Mg2Zn 11 The diffraction peak of T-BTO is clearly present in the T-BTO-Zn-0.8Mg composite material, indicating that we have successfully incorporated T-BTO into the Zn-0.8Mg alloy. We then further observed the distribution of BTO in the alloy through SEM, as shown in Figure 2. Figure 8 As shown in Figure b, the size of T-BTO particles is 0.5 to 1 μm, and they are evenly dispersed in the alloy without obvious agglomeration. The above results show that the T-BTO-Zn-0.8Mg composite material with uniform BTO distribution was successfully synthesized.
[0115] Furthermore, the piezoelectric performance of the T-BTO particles used was tested using a piezoresponse force microscope (PFM). Figure 9 Figure a is the piezoelectric response phase hysteresis loop diagram, which shows that the BTO phase voltage signal has an obvious 180° phase shift; Figure b is the amplitude butterfly loop diagram, which shows that a butterfly-shaped hysteresis loop is obtained in the voltage range of -6V to 6V, indicating that the BTO particles we use have a typical piezoelectric response.
[0116] In addition, the prepared Zn-0.8Mg and T-BTO-Zn-0.8Mg composites were cut into samples of 5*5*5mm size. Figure 10 The device shown in a was subjected to a dynamic load (20 MPa, 1 Hz) for 1 hour to test the weight loss rate of the sample. Figure 10 As shown in b, the average weight loss rate of Zn-0.8Mg alloy is about 2.04 mg / cm 2 The average weight loss rate of the T-BTO-Zn-0.8Mg composite material is about 3.73 mg / cm 2 ,The above results show that piezoelectric materials can be ,uniformly distributed in the degradable alloy in the form of nanoparticles to ,achieve piezoelectric response intelligent degradation.
[0117] In summary, the composite material of the present invention promotes the intelligent release of metal ions in the metal ion releasing material through the piezoelectric response of the piezoelectric material.
[0118] The above embodiments are only intended to help understand the method and core concept of the present invention. It should be noted that, without departing from the principles of the present invention, a number of improvements and modifications may be made to the present invention by those skilled in the art, and such improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A composite material, characterized in that: It is obtained by compounding piezoelectric material and metal ion releasing material; The metal ion releasing material is selected from one or more of magnesium-based degradable alloys, iron and iron-based degradable alloys, zinc and zinc-based degradable alloys.
2. The composite material according to claim 1, characterized in that The mass percentage of the piezoelectric material in the composite material is 1% to 15%.
3. The composite material according to claim 1, characterized in that The piezoelectric material is selected from one or more of tetragonal barium titanate, zinc oxide, and molybdenum sulfide.
4. The composite material according to claim 1, characterized in that The magnesium-based degradable alloy is selected from Mg 60 Zn 35 One or more of Ca5 amorphous alloy, MgZnCaSr amorphous alloy, MgZnYNd alloy, MgYReZr alloy, MgZnCa alloy, MgZnSr alloy, MgZnCaSr alloy, and MgZnCu alloy; The iron-based degradable alloy is selected from FeZn series alloys and / or FeMn series alloys; The zinc-based degradable alloy is selected from one or more of ZnMg series alloys, ZnCa series alloys, ZnCu series alloys, ZnMn series alloys, ZnLi series alloys, and ZnRe series alloys.
5. The composite material according to claim 1, characterized in that The piezoelectric material is selected from tetragonal barium titanate; The metal ion releasing material is selected from Mg 60 Zn 35 One or more of Ca5 amorphous alloy, iron, zinc, and zinc-based degradable alloy.
6. The composite material according to claim 5, characterized in that The zinc-based degradable alloy is selected from Zn-Mg alloy, wherein the mass percentage of Mg is 0.1% to 0.8%.
7. The method for preparing the composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: The composite material is obtained by compounding the piezoelectric material and the metal ion releasing material through a magnetron sputtering method, a melting method or a 3D printing method.
8. The preparation method according to claim 7, characterized in that: The magnetron sputtering method comprises the steps of uniformly sputtering the piezoelectric material onto the surface of the substrate by a first magnetron sputtering and uniformly sputtering the metal ion releasing material onto the surface of the piezoelectric material by a second magnetron sputtering to prepare the composite material; The smelting method comprises mixing and smelting the metal ion releasing material and the piezoelectric material to obtain the composite material; The 3D printing method comprises uniformly mixing piezoelectric material powder and metal ion releasing material powder, and then performing laser melting molding through 3D printing to obtain the composite material.
9. An implant, comprising the composite material according to any one of claims 1 to 6 or the composite material prepared by the preparation method according to claim 7 or 8.
10. Use of the implant according to claim 9 in biomedical degradable stents, biomedical degradable suture materials, degradable orthopedic implants, degradable dental materials, degradable self-powered electronic bandages, and degradable electrodes.
Citation Information
Patent Citations
Preparation method for controllable degradation type zinc-magnesium gradient material
CN110449579A
Biomedical titanium material suitable for ultrasonic therapy, and preparation method and application thereof
CN107773783A
Piezoelectric nano composite material and preparation method thereof
CN110797453A
Degradable zinc-based alloy for orthopedic implants and preparation method of degradable zinc-based alloy
CN115261672A
Tissue scaffolds and constructs
US20230390461A1
Cited By
Intelligent degradable three-dimensional porous scaffold with piezoelectric activity as well as preparation method and application of intelligent degradable three-dimensional porous scaffold
CN120939284A
A piezoelectrically active smart biodegradable three-dimensional porous scaffold, its preparation method and application
CN120939284B